(3hUjI GdSgQhQOjs - (3GdSgQhQOj, TgGH GdOjf, YeQ GdSgQhQOj, J(B586(3g`s ((3CZQhS (B((3GdbSWfWjfjI(B)s)
(3ChdgG (B:s
(3jG Hfj ChUjc HJbhi Gddg hNTjJg aj GdSQ hGdYdGfjI hdRhe Mb Gddg JYGdi hQShdg hMb GdeTGjN CLeYjfs
(3BNQgG (B:s
(3hYO faSc ef CUMGH GdbHhQ hGNQL efgG ceG ONdJgG aEfc dG JOQj eG GSec ZOG jhe GdbjGeIs
(3aj BNQg fbhd aj GdCOH hGdTYQ HNW GdMGLj EHQGgje Hf HTQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 140s
(3eYLe GdeDdajf(B: 2 / 574s
(3cTa GdXfhf(B: 1 / 872s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs